Ecological Risk Assessment of Watersheds Based on Adaptive Cycling Theory—A Case Study of Poyang Lake Ecological and Economic Zone - Yixi Gu; Jiaxuan Wang; Xinyi Su; Kaili Zhang (Land)
Under the global urbanization context, irrational land use patterns have exacerbated ecosystem imbalance. Developing watershed ecological risk assessment methods based on adaptive cycle theory holds significant scientific importance for flood risk prevention. This study established a watershed ecological risk assessment framework within the adaptive cycle framework, focusing on the Poyang Lake Ecological Economic Zone in the middle-lower Yangtze River Basin. The results revealed that high-risk ecological areas clustered around the Poyang Lake water system with scattered urban distribution, while medium-risk zones dominated the study area. Low-risk regions primarily concentrated in the Yuanhe Plain of southwestern region. The system exhibited significant spatial heterogeneity in “exposure” and “disturbance” risks. Medium–high exposure pixels accounted for 43.3% with a dispersed distribution, whereas disturbance pixels concentrated in Poyang Lake waters and developed urban areas (64.34%), indicating that disturbance exerted a stronger influence on risk assessment outcomes. Governance practices demonstrated that policy preferences may introduce biases into watershed ecological risk evaluations. Multi-scenario simulations using an Ordered Weighted Averaging (OWA) algorithm identified risk-uncertain zones in southeastern hilly areas and northern Poyang Lake waters, while distinguishing stable high/low-risk regions unaffected by decision-making influences. These findings provide critical references for formulating sustainable watershed management strategies.